الأبعاد الفنية والموضوعاتية في قصيدة الهايكو المجموعة الشعرية لـ لخضر توامة "أنموذجا - شويه, الشيماء; معطى الله, ايمان; نصرات, فؤاد (جامعة الوادي - University of Eloued, 2023)
الملخص: تناول موضوع بحثنا المعنون بـ "الأبعاد الفنية والموضوعاتية في قصيدة الهايكو للمجموعة الشعرية لخضر توامة", فقصيدة الهايكو من الأشعار العربية المعاصرة التي ضربت جذورها في الحضارات اليابانية ومنها انتقلت إلى اللغة الإنجليزية والفرنسية وأخيرا إلى العربية, التي حُرِّرَت في عدَّة دواوين وكُتُبْ منها "شغف المساء" لشاعر الجزائري لخضر توامة، وأيضا مجموعات إلكترونية وخاصة على مواقع التواصل الاجتماعي, التي شملت مواضيع عديدة منها الطبيعة التي كانت مصدر إلهام لشعراء الهايكو, ثم المرأة منبع الحنان والعطاء التي يستقى منها موضوع الحب الذي ينبعث من داخلها بكل صدق وإخلاص, أما عن وفاء الشاعر "لخضر توامة" للعروبة تجلى في حبه ودفاعه عن فلسطين التي وسمها بتعابير كثيرة, تبعه الحقل الديني الذي كان أساس الحياة ومنبعه القلب والقرارات النفسية الخاصة, وهاته لها خصائص فنية تميزها عن باقي الأشعار منها المشهدية التي تطرح مشهدين أحدهما حاضر والآخر غائب, ولا ننسى البناء الإيقاعي دوما هو من يبرز في بناء الأشعار لم يكن شعر الهايكو كبقية الأشعار لا وزن له ولا نظام, والتكثيف الدلالي والإيجاز هم من ميزوه من بين الأشعار . وكل هذه المواضيع التي قدَّمها الشاعر "لخضر توامة" في كتابه "شغف المساء" كانت مواضيع متجانسة بسمات فنية وبطريقة أدبية تخص شعر الهايكو. Résumé : فرنسية أو انجلزية The topic of our research, entitled "Technical and thematic dimensions of the Haiku poem of the verse collection of Khader Twama" The Haiku poem is a contemporary Arabic poem that has its roots in Japanese civilizations, from which it has moved to English, French and finally to Arabic, which has been edited in several Dowain and written. "The passion of the evening" by the Algerian poet Lakhdar Tama, as well as electronic groups, especially on social media sites, which included many subjects, including nature, which inspired Haiku poets, and then women, the source of tenderness and giving from which the subject of love emanates from them in all sincerity and sincerity, as well as the loyalty of the poet "Lakhdar Umama" for Arabism manifested in his love and defence of Palestine, which he called many expressions. It was followed by the religious field, which was the basis of life, the source of the heart and the psychological decisions of private, It has artistic characteristics that distinguish it from other poems, including the spectacle of two scenes, one present and the other absent. And don't forget, rhythmic construction always stands out in the construction of poetry. Haiku hair like all other poetry was neither weighing nor system. Semantic intensification and brevity are among the poems. All these subjects presented by the poet "Lakhdar Toama" in his book "Evening Passion" were harmonious themes with artistic and literary attributes of haiku poetry.
Keywords: عربيّــة: شعر الهايكو, لخضر توامة ، الطبيعة, التكثيف ،الإيجاز, المرأة, الصورة.; Haiku Hair, Greens Twin, Nature, Condensation, Brevity, Women, Photo.